Sherlock Holmes : a game of shadows [videorecording (DVD)] - Ritchie, Guy; Downey, Robert, Jr., 1965-; Law, Jude, 1972-; Rapace, Noomi, 1979-; Harris, Jared, 1961-; Marsan, Eddie; McAdams, Rachel, 1978- (Warner Home Video, 2012)
Sherlock Holmes has always been the smartest man in the room, until now. There is a new criminal mastermind at large, Professor James Moriarty, and not only is he Holmes's intellectual equal, but his capacity for evil, coupled with a complete lack of conscience, may give him an advantage over the renowned detective. Holmes's investigation into Moriarty's plot becomes more dangerous as it leads him and Watson out of London to France, Germany, and finally Switzerland.